ANALISIS FRASA BERDASARKAN GOLONGAN KATA TERHADAP TEKS BERITA “SAAT INTERNET JADI KAMBING HITAM TERHAPUSNYA REKAMAN CCTV TRAGEDI KANJURUHAN” - Dini Karwati; Wulansari Wulansari (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
Syntax is a branch of linguistics that examines grammar, one of which is the focus of researchers on the issue of the types of phrases used in news texts. The method used in this research is descriptive qualitative, where the data is explained or presented systematically. Based on the results of the analysis found 5 verb phrases, 4 prepositional phrases, 5 numeral phrases, 2 pronoun phrases, 2 conjunction phrases, and 5 noun phrases. Based on the distribution equation or word category, there are seven groups, namely: noun phrases, verb phrases, adjective phrases, pronoun phrases, numeral phrases, prepositional phrases, and conjunction phrases. Researchers expect readers to study and understand the results of this analysis and apply them in a good and correct language context.